EFEKTIFITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPAS SDN 11 AMPENAN - Miranti, Aulia; Siti Istiningsih; Muhammad Sobri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of fourth-grade students in the Science and Social Studies (IPAS) subject at SDN 11 Ampenan. The teacher centered learning approach resulted in students being less activelye engaged in the learning process, which led to a low level of conceptual understanding. One alternative to address this problem is the implementation of the Project Based learning (PjBL) model, which emphasizes students’ active participation throught Project Based Learning (PjBL) activities. This study aimed to determine the effectiveness of the Project Based Learning (PjBL) model on the learning outcomes of fourth grade students in the Science and Social Studies (IPAS) subject at SDN 11 Ampenan. This study employed a quantitative approach using a quasi-experimentresearch method with anon-equivalent Control Group Design. The population consisted of all fourth grade students at SDN 11 Ampenan. Data were collected through test and observation. The data were analysed using validity testing, reliability testing, normality testing, hypothesis testing (paired sample t-test), and N-Gain test to determine the effectiveness of the implementation of the learning model. The results of the study indicated that the implementation of the Project Based Learning (PjBL) model had a significant effect on students’ learning outcomes. The hypothesis test produced a significance value of 0,021 (< 0,05), indicating that the alternative hypothesis was accepted. Furthermore, the N-Gain analysis yielded an average score of 66,69% which was categorized as moderately effective. The implementation of the Project Based Learning (PjBL) model also improved students’ learning engagement, learning motivation, critical thinking skills, collaboration, communication, and active participation throughout the learning process. Based on these finding, it can be concluded that the Project Based Learning (PjBL) model is moderately effective in improving in the learning outcomes of fourth grade students in the Science and Social Studies (IPAS) subject at SDN 11 Ampenan.